2022
DOI: 10.1111/tmi.13816
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with antiretroviral therapy use among pregnant women in rural and urban settings in Southern Province, Zambia: 2016–2019

Abstract: Objectives To assess antiretroviral therapy (ART) coverage among pregnant women living with HIV and compare the characteristics of women who received and did not receive ART during pregnancy in Zambia. Methods A cross‐sectional study was conducted at urban and rural health facilities in Southern Province, Zambia, from 2016 to 2019. Pregnant women living with HIV delivering at study sites were enrolled and administered a questionnaire, and the results of infant diagnostic testing for HIV at birth was documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…A large study of pregnant women living with HIV in Southern Province found that women who did not receive ART were younger, more likely to be diagnosed with HIV during pregnancy, and less likely to have disclosed their status to their partner or received antenatal care. 25 Increased efforts to ensure repeated testing during pregnancy and counseling for women newly diagnosed with HIV during pregnancy, as well as potential inclusion of pre-exposure prophylaxis in services offered to pregnant women, may be needed to further reduce new pediatric infections.…”
Section: Discussionmentioning
confidence: 99%
“…A large study of pregnant women living with HIV in Southern Province found that women who did not receive ART were younger, more likely to be diagnosed with HIV during pregnancy, and less likely to have disclosed their status to their partner or received antenatal care. 25 Increased efforts to ensure repeated testing during pregnancy and counseling for women newly diagnosed with HIV during pregnancy, as well as potential inclusion of pre-exposure prophylaxis in services offered to pregnant women, may be needed to further reduce new pediatric infections.…”
Section: Discussionmentioning
confidence: 99%
“…Studies worldwide have reported factors that have an association with maternal HIV test and ART services uptake, including place of residence [24][25][26], education level [24,[26][27][28], maternal age [26,27], knowledge of HIV/AIDS and PMTCT [27,29,30], SES [24,26,31,32], lack of privacy and confidentiality [33], women's decision-making capacity [29,34,35], prenatal care [26,31], fear of disclosure and stigma [30,[36][37][38][39]. Likewise, factors such as distance from a health facility [40], partner/family support [39], denial of HIV status [41], shortages of resources [41,42], lack of knowledge [43], feelings of guilt [43], children of known HIV positive fathers [44] and maternal receipt of ART/HAART [40,43,45] have also been reported to affect infant ARV prophylaxis and EID services uptake.…”
Section: Introductionmentioning
confidence: 99%